The relationship between third year students' concept of nursing and their clinical performace - Cortina, Grace F.; Guianan, Darwin T.; Noble, Melissa R.; Remigio, Irene Claudette A.; Sison, Zhasmin M. (Manila College of Nursing University of the Philippines Manila, 1997)
Nursing is most of the time used synonymously with service and caring. As such, nursing students -- third year students in this study -- are expected to at least have a concrete and well-defined concept of nursing, defined in this study as being the role of the nurse. The researchers assumed that a student who knows his or her role as a nurse will perform well in clinical as reflected by their grades in a nursing subject.

With these, the research aims to look if there is a relationship between the concept of nursing and the clinical performance of University of the Philippines College of Nursing Third Year Nursing students. The study focused on third year students since this year considered the as the last year for learning skills with the fourth year usually called as mastery of skills. The sample was determined through simple random sampling. The tool used is a questionnaire. A consent was taken since students’ N-105 grades were used a data.

Pearson test for correlation was the test statistic with the value of r =0.018 interpreted as low negative correlation meaning third year nursing students’ concept of nursing does not affect their clinical performance.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, March 1997.
Keywords: Nursing -- Research